(untitled) (Advancements in Homeopathic Research, 2024)
After successful demonstration in their previous four publications that patients of chronic kidney disease (CKD) and acute renal failure (ARF) can be managed by homoeopathic treatment, Gupta et. al. herewith put forth another episode of this case series. This fifth case series is on successful management of CKD patients by maintaining their serum creatinine level and eGFR within a reasonable range, delaying further deterioration and improving their quality of life for a considerable period of time without haemodialysis. The first two cases in this series are of 62-year and 59-year old hypertensive, diabetic males with CKD in whom S. Creatinine level was maintained for about 7 and 3 years respectively. In third case of a 47-year old hypertensive, non-diabetic male, S. Creatinine level was maintained without haemodialysis for more than 2 years.